Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Fintech Syariah Terhadap Perilaku Keuangan pada Gen Z - Anitia Avetri; Herlina Yustati; Debby Arisandi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the influence of financial literacy, financial inclusion, and sharia financial technology on the financial behavior of generation Z in Bengkulu City. In this study, used quantitative associative research methodology, 397 respondents were selected from a sample size of 40,401 people using purposive sampling techniques calculated using the slovin formula and a margin of error of 5%. The data source uses primary data collected through questionnaires and analyzed using SPSS software version 22. Partially, the results of the study indicate that the financial behavior of Generation Z is significantly influenced by the variables of financial literacy and sharia financial technology, while the variable of financial inclusion does not influence the financial behavior of Generation Z. Together, the three independent variables have a significant effect on the dependent variable, with a coefficient of determination (R2) of 25,9%, which explains that in addition to variables of financial literacy, financial inclusion, and sharia financial technology, there are many other factors that influence variables of financial behavior.